Relationship between hyoid bone and pharyngeal airway in different skeletal patterns - Jung-Hsuan Cheng; Szu-Yu Hsiao; Chun-Ming Chen; Kun-Jung Hsu (Elsevier, 2020)
Background/purpose: The hyoid bone and its attached muscles play an important role in the maintenance of the pharyngeal airway space. The aim of the present study was to investigate the correlations between hyoid bone and pharyngeal airway spaces among three skeletal patterns. Materials and methods: Cephalograms of 90 male and 90 female were divided into skeletal patterns: Class I, Class II, and Class III. The following pharyngeal airway spaces were measured: SP, soft palate related pharyngeal airway; BP, B point related pharyngeal airway; C2P, second cervical vertebra related pharyngeal airway; and LP, laryngopharyngeal airway. The paired t-test, one-way analysis of variance, and Pearson correlation analysis were used in the statistical analyses. Results: SP was significantly longer in Class III (12.4 mm) than in Class I (10.7 mm) and Class II (9.5 mm), and BP was significantly greater in Class III (16.3 mm) than in Class II (12.4 mm). The hyoid bone had a significantly anterior location in Class III compared to Class II, whereas vertical positions of the hyoid bone showed no significant differences among the three skeletal patterns. Among female with a Class III skeletal pattern, the horizontal position of the hyoid bone had a positive moderate, significant correlation with the C2P, whereas among male, this was not observed. Conclusion: The location of the maxilla (SNA) was not significantly correlated with the pharyngeal airway space. However, the more protruding the mandible (SNB) is, the more anterior the hyoid bone and the longer the pharyngeal airway will be.